Isolation and characterization of peroxidase P7-like gene and Rab-GDI like gene from potential medicinal plants: A step toward understanding cell defense signaling - Jabeen, Raheela; Iqbal, Atia; Deeba, Farah; Zulfiqar, Faisal; Mustafa, Ghulam; Nawaz, Haq; Habiba, Ume; Nafees, Muhammad; Zaid, Abbu; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Defensin genes form part of a plant’s defense system and are activated when exposed to biotic or abiotic stress. They play a vital role in controlling many signaling pathways involved in various plant defense mechanisms. This research aimed to isolate and characterize novel defensin genes from selected medicinally important plants to explore their signaling mechanisms and defense associated roles for breeding. The DNA of Albizia lebbeck and Moringa oleifera was subjected to PCR amplification using gene-specific primers of defensin genes. Two novel defensin genes were isolated in each species, with sequence lengths of 300 bp in A. lebbeck and 150 bp in M. oleifera. The Iin- silico/bioinformatic analysies undertaken to retrieve and align their orthologous sequences revealed 100% similarity of the A. lebbeck gene with the Musa acuminate peroxidase P7-like gene and 85% similarity of the M. oleifera gene with the Manihot esculenta GDP dissociation inhibitor gene. The reliability, stability and physiochemical properties of homology models of these sequences was confirmed through online computational studies. using PROCHECK and ProSA. This study preliminary study confirmed the presence of novel genes with peroxidase P7 and Rab GDP dissociation inhibitor gene-like activity in A. lebbeck and M. oleifera, respectively, and their potential defense role in plants. Thus, the defensin genes of both species could be used in the synthesis of transgenic self-defensive plants with increased disease resistance and as potential candidates for improved crop production and thraputic formulation in the future.